Implementation of Problem-Based High School Chemistry Textbooks on Improving Student Learning Outcomes and Motivation on Acid-Base Subject Materials - Siregar, Nia Ramadhani; Dibyantini, Ratu Evina (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to determine the effect of the implementation of Problem-Based High School Chemistry Textbooks on improving student learning outcomes and learning motivation, as well as finding out the correlation between the two in acid-base materials. The research was carried out at SMA Negeri 4 Medan using a quasi-experimental pretest-posttest control group design. The research sample was 72 students consisting of experimental classes (XI-7) and control classes (XI-11), totaling 36 students each, which were selected using random sampling techniques. Data were collected through pretest, posttest, and learning motivation questionnaires. The results showed that the average pretest and posttest scores of the experimental class were 49.11 and 89.66 with an N-gain of 0.78 or 78% (high category), higher than the control class that obtained an average of 48.89 and 64.55 with an N-gain of 0.31 or 31% (medium category). The average initial and final motivation of the experimental class were 48.38 and 84.90 with an N-gain of 0.70 or 70% (high category), higher than that of the control class which obtained an average of 45.75 and 63.44 with an N-gain of 0.31 or 31% (medium category). The results of the hypothesis test showed that the Problem-Based High School Chemistry Textbook had a significant effect on improving student learning outcomes and motivation. In addition, there was a high positive correlation (r = 0.789) between learning outcomes and student learning motivation. Thus, the implementation of the Problem-Based High School Chemistry Textbook has proven to be effective in improving student learning outcomes and motivation on acid-base materials.